‘Culture’s Consequences’: Implementing Western ideas in an Asian Organisation - Retna, Kala; Bryson, Jane (School of Management Working Papers, 2003)
This paper briefly reviews the connection between knowledge management and the learning organisation, argues that both concepts rely on culturally embedded theories and practices, and presents a case study of the use of Senge’s learning organisation concepts in one large Singaporean organisation. The analysis of this case reveals the cultural challenges that emerged in the process of applying essentially Western management theories within an Asian culture. In conclusion we discuss the practical implication of these challenges for Singapore organisations, multi-national organisations, and for trans-national consulting advice. In particular, Singaporean respect for power, status and order impacts on knowledge management implementation strategies. Thus, for instance, we suggest same status groups be used for seeking feedback. At a more general level we discuss the choice knowledge management practitioners have between ‘best practice’ versus ‘best fit’ approaches to implementation.